Enhanced Functional Genomic Screening Identifies Novel Mediators of Dual Leucine Zipper Kinase-Dependent Injury Signaling in Neurons - Welsbie, Derek S; Mitchell, Katherine L; Jaskula-Ranga, Vinod; Sluch, Valentin M; Yang, Zhiyong; Kim, Jessica; Buehler, Eugen; Patel, Amit; Martin, Scott E; Zhang, Ping-Wu; Ge, Yan; Duan, Yukan; et al. (Neuron (Cambridge, Mass.), 2017)
Dual leucine zipper kinase (DLK) has been implicated in cell death signaling secondary to axonal damage in retinal ganglion cells (RGCs) and other neurons. To better understand the pathway through which DLK acts, we developed enhanced functional genomic screens in primary RGCs, including use of arrayed, whole-genome, small interfering RNA libraries. Explaining why DLK inhibition is only partially protective, we identify leucine zipper kinase (LZK) as cooperating with DLK to activate downstream signaling and cell death in RGCs, including in a mouse model of optic nerve injury, and show that the same pathway is active in human stem cell-derived RGCs. Moreover, we identify four transcription factors, JUN, activating transcription factor 2 (ATF2), myocyte-specific enhancer factor 2A (MEF2A), and SRY-Box 11 (SOX11), as being the major downstream mediators through which DLK/LZK activation leads to RGC cell death. Increased understanding of the DLK pathway has implications for understanding and treating neurodegenerative diseases.